Wear-resistance enhancement of nanostructured W-Cu-Cr composites. (December 2021) - Cao, Lijun; Hou, Chao; Tang, Fawei; Han, Tielong; Huang, Xintao; Li, Yurong; Wu, Gaochao; Liu, Chao; Liang, Shuhua; Luan, Junhua; Jiao, Zengbao; Nie, Zuoren; et al.
Abstract: Nanostructured W-Cu-Cr composites were fabricated, which exhibit exceptionally high hardness (~1000 HV) as compared with those of the conventional W-Cu composites, due to the combined advantages of Cr dissolution, precipitate formation and grain refinement. Nonmonotonic variation of the wear resistance with hardness was discovered. With an appropriate content of Cr, the preferential oxidation reduced the oxidation of W. Moreover, it facilitated formation of a stable protective film with fish-scale morphology and also refined the structure, leading to a high microhardness at the worn surface. The wear rate (1.65 × 10 −6  mm 3  N −1  m −1 ) was reduced by an order of magnitude compared with that of the conventional counterpart. However, excessive addition of Cr may deteriorate the wear resistance in spite of a higher hardness due to the embrittlening of W phase and difficulty to form a stable protective film at the worn surface. This study provides a new strategy for developing W-Cu composites with outstanding wear resistance. Highlights: Outstanding wear resistance of nanostructured W-Cu-Cr composite was achieved. Nonmonotonic variation of wear resistance with hardness was discovered. Mechanisms were proposed for the enhancement of wear resistance. Effects of both strengthening and embrittlening of Cr addition were revealed.